O problema da fundamentação racional da moral e do direito em Kant - Rauber, Gládis Maria (2008)
This study attempts to elucidate, in a first moment, the origin and the development of the moral problem in Kantian philosophy, from the Critique of Pure Reason to the Metaphysics of Morals, and the solution that Kant gave to it. Aiming to establish the Kantian rational groundwork of moral and right, this research turns, then, to the development of the main question that permeates throughout Kantian philosophy: How are a priori synthetic judgments possible? determining the conditions of possibility of such judgments in each one of the fields, the theoretical and the practical. Our goal is to elucidate that, although the right must not be confused with moral, demanding only legal conformity, that is, non-subjective adhesion of the actions to the law, it is subordinated to the moral in the measure that this right is based on a formal universalism of the supreme criterion of the morality, that is, the categorical imperative